Optimization of Dehumidification Air Flow Distribution in Temulawak Tray Dryer with Computational Fluid Dynamics - Ridwan; Apriansa, Farul; Irawan, Rudi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2024)
Temulawak (Curcuma xanthorrhiza Roxb.), a member of the Zingiberaceae family, has long been recognized as a medicinal plant with a moisture content approximately 80-90%. The high moisture content of temulawak renders it challenging to store for extended periods without drying. Temulawak is susceptible to heat damage due to the potential for thermal degradation of its internal components. Accordingly, it can be concluded that low-temperature and low-air-humidity drying conditions are required. Furthermore, one of the most suitable methods is the use of a dryer that incorporates a dehumidification process. The objective of this research is to develop a temulawak dryer design and simulation variations of the incoming velocity of air flow to obtain the most optimal drying chamber by incorporating a vertical airflow channel. A design and simulation for a temulawak dryer were created using the 2022 version of SolidWorks software (flow simulation modul). The design started from drawing two-dimension, then three-dimension, and determining boundary condition and meshing. A fluid temperature of 35.7°C and a relative humidity (RH) of 22% were used to model the drying process at varying airflow velocities of 1.5 m/s, 2 m/s, and 2.5 m/s. The drying chamber, with dimensions of 676 mm x 406 mm and height of 806 mm, was designed using the type AISI 304 and achieved the most optimal airflow distribution results at a velocity of 2.5 m/s, exhibiting a relatively higher fluid temperature than the other two airflow velocity variation.